Reference Point Adaptation and Disposition Effect - CHIYACHANTANA, Chiraphol New (Institutional Knowledge at Singapore Management University, 2013)
This paper investigates the importance of reference point adaptation in the analysis of the disposition effect. We consider two exogenous factors pertinent to reference point adaptation: prior outcome and recent expectation of future outcome. We show that the incidence of the disposition effect varies in a manner consistent with reference point adaptation. Both prior outcome and recent expectation of future outcome affect the location of the reference point and have a large and significant impact on the incidence of the disposition effect. First, the disposition effect can largely be explained by investors’ inability to sufficiently adapt the reference point in response to large capital losses. Second, a negative expectation of future outcome, due to recent unfavorable information and highly speculative investments, accelerates reference point adaptation to price depreciation and dramatically increases loss realization. These effects are economically sizeable and are robust to plausible heterogeneity concerns and alternative explanations such as a belief in mean-reversion and managerial incentives.